Navigation by Judgment: Why and when Top Down Management of Foreign Ai d Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of d ollars annually, with mixed results. Part of the problem in these ende avors lies in their execution. When should foreign aid organizations e mpower actors on the front lines of delivery to guide aid intervention s, and when should distant headquarters lead? In Navigation by Judgmen t, Dan Honig argues that high-quality implementation of foreign aid pr ograms often requires contextual information that cannot be seen by th ose in distant headquarters. Tight controls and a focus on reaching pr e-set measurable targets often prevent front-line workers from using s kill, local knowledge, and creativity to solve problems in ways that m aximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eig ht paired case studies of development projects, Honig concludes that a id agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately m easure. Highlighting a crucial obstacle for effective global aid, Navi gation by Judgment shows that the management of aid projects matters f or aid effectiveness.